Outbreak of Oropouche Virus in French Guiana - Mélanie Gaillet; Clara Pichard; Johana Restrepo; Anne Lavergne; Lucas Perez; Antoine Enfissi; Philippe Abboud; Yann Lambert; Laurence Ma; Marc Monot; Magalie Demar; Felix Djossou; et al. (Emerging Infectious Diseases, 2021)
Oropouche fever is a zoonotic dengue-like syndrome caused by Oropouche virus. In August–September 2020, dengue-like syndrome developed in 41 patients in a remote rainforest village in French Guiana. By PCR or microneutralization, 23 (82.1%) of 28 tested patients were positive for Oropouche virus, documenting its emergence in French Guiana.